Idiopathic spinal cord herniation of the cervical cord: unusual cause of proximal muscle weakness in upper limbs. (17th May 2016) - Rajapakse, Dilina; Mapara, Leah; Maniharan, Sathiyaseelan
Abstract : Idiopathic spinal cord herniation (ISCH) is a recognised rare cause of progressive and potentially curable myelopathy. Around 170 cases have been described in the literature, all to be found between the T2 and T8 vertebrae. We report a case of ISCH in the cervical region. A 23-year-old man with no history of trauma presented with a 6-year history of bilateral mild resting hand tremor and left scapular pain radiating to the left arm for a duration of 8 months. Nerve conduction studies showed some denervation changes of the upper limbs and bulbar regions. MRI of the spine showed anterior midline herniation of the spinal cord at the level of C7 vertebra with an associated collection of cerebrospinal fluid in the extradural space in the cervical region. Owing to the non-progressive nature of symptoms, currently the patient is managed conservatively.